Near-Surface Ground Ice Conditions In University Valley, McMurdo Dry Valleys of Antarctica. - Lapalme, Caitlin (Université d'Ottawa / University of Ottawa, 2015)
This study aims to quantify ground ice content and describe the cryostructures and sediment in 15 ice-bearing permafrost cores collected from nine sand-wedge polygons in University Valley. The objectives were reached through laboratory measurements and computed tomodensitometric (CT) scanned image analysis of the permafrost cores. The soils in the valley were predominantly medium-sand. Four types of cryostructures were present in the cores: structureless, suspended, crustal and porphyritic. Excess ice content ranged from 0 to 93%, gravimetric water content ranged from 13 to 1881% and volumetric ice content varied from 28 to 93%. Median excess ice, volumetric ice and gravimetric water contents significantly increased in the top 20 cm of the cores taken from the polygon shoulders with increasing distance from University Glacier. Ground ice was preferentially stored in the centre of the investigated polygons where the ground surface remains cryotic throughout the year. Conversely, higher ground ice contents were measured in the shoulders of the investigated polygon where the ground surface is seasonally non-cryotic. CT-scanned images were shown to reasonably assess the distribution and presence of excess ice in permafrost cores taken from a cold and hyper-arid environment. The results of this thesis provide the first cryostratigraphic study in the McMurdo Dry Valleys of Antarctica.